Role of fine needle aspiration cytology in the preoperative diagnosis of malignancy in parotid and submandibular gland neoplasm (Bangladesh Journal of Otorhinolaryngology, 2014)
Objective: To evaluate the role of Fine Needle Aspiration Cytology in the preoperative diagnosis of malignancy in parotid and submandibular gland neoplasm. Methods: This cross sectional study on 50 cases was conducted in the Department of Otolaryngology and Head-Neck Surgery of Sir Salimullah Medical College Mitford Hospital and Dhaka Medical College Hospital from January2009 to June 2010. Results: Fine needle aspiration cytology findings of our all 50 cases were compared with postoperative histopathological reports. Out of the 50 cases, in 36(72%) cases of benign neoplasm and 7(14%) cases of malignant neoplasm, pre-operative FNAC findings and post operative histopathological findings were same. In 7 cases, FNAC and post operative histopathological findings did not matched. These were 2 (4%) false positive and 5 (10%) false negative result.In our study sensitivity of FNAC for reporting malignancy was 58.33%, specificity to rule out malignancy was 94.73% and overall accuracy in detecting malignant tumour was 86%. Positive predictive value and negative value were 77.77% and 87.80% respectively. It can be concluded that fine needle aspiration cytology is a safe, cheap and useful preoperative diagnostic tool in the diagnosis of malignancy in parotid and submandibular gland, but as fine needle aspiration cytology partly depends on operator skill, it may give false negative and false positive result. Conclusion: FNAC is a useful preoperative diagnostic tool for malignant parotid and submandibular glands with high specificity and sensitivity. DOI: http://dx.doi.org/10.3329/bjo.v19i2.17634 Bangladesh J Otorhinolaryngol 2013; 19(2): 110-118